Optimizing Electrode Montages of Transcranial Direct Current Stimulation for Attentional Bias Modification in Early Abstinent Methamphetamine Users - Shahbabaie, Alireza; Hatami, Javad; Farhoudian, Ali; Ekhtiari, Hamed; Khatibi, Ali; Nitsche, Michael A. (Frontiers in Pharmacology, 2018)
Introduction: Chronic use of most psychoactive drugs may lead to substance dependence and drug addiction. Drug addiction is a chronically relapsing disorder, and current pharmacological and behavioral therapies are not fully efficient. Attentional bias (AB) is hypothesized to have a causal contribution to substance abuse, addiction development and, maintenance. Transcranial direct current stimulation (tDCS) has been of increasing interest in the past few years as a means for modulating neuroplasticity of the human brain. Although several studies have reported promising therapeutic effects for tDCS in drug abusers, there is no consensus about optimal electrode montages and target brain regions. This study was aimed to compare effectiveness of several electrode montages in modifying AB. Methods and Materials: Ninety early-abstinent Methamphetamine users were recruited from several residential drug-rehabilitation centers in Tehran province. They were randomly assigned to six groups with different electrode montages, targeting the left or right dorsolateral prefrontal cortex (DLPFC) as follows: Two conditions with anodal tDCS over the right DLPFC (return electrode placed over the left shoulder or left supraorbital ridge), three conditions with the anode positioned over the left DLPFC (return electrode over the right shoulder, right supraorbital ridge, or contralateral DLPFC), and one sham condition. Active stimulation intensity was 2mA DC, delivered for 13 minutes followed by a 20-minute rest and another 13 minutes of stimulation. The probe detection task (PDT) was performed to assess AB. The positive and negative affect scale (PANAS), and the depression anxiety stress scales (DASS) were used to assess baseline affective status before the intervention. Results: Mixed model analysis showed that the left DLPFC /right shoulder and left DLPFC/right DLPFC montages reduced AB toward drug-cues in comparison with sham stimulation. Conclusion: Our findings indicate that anodal stimulation over the left DLPFC reduces AB in methamphetamine users. Furthermore, according to specific current flow direction and electric field orientation determined by the position of the return electrode, stimulation may affect different dimensions of AB. This study offers promising findings for further studies investigating tDCS as a clinical device to modify AB in drug users.